2011
DOI: 10.3762/bjnano.2.80
|View full text |Cite
|
Sign up to set email alerts
|

Generation and agglomeration behaviour of size-selected sub-nm iron clusters as catalysts for the growth of carbon nanotubes

Abstract: SummaryMass-selected, ligand-free FeN clusters with N = 10–30 atoms (cluster diameter: 0.6–0.9 nm) were implanted into [Al@SiOx] surfaces at a low surface coverage corresponding to a few thousandths up to a few hundredths of a monolayer in order to avoid initial cluster agglomeration. These studies are aimed towards gaining an insight into the lower limit of the size regime of carbon nanotube (CNT) growth by employing size-selected sub-nm iron clusters as catalyst or precatalyst precursors for CNT growth. Aggl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…The growth conditions (gas flow, heating and cooling rate, water flow, etc.) are described in [31][32][33]. TEM did not show deposition of amorphous carbon on the walls of the as-grown CNTs (Fig.…”
Section: Synthesis and Purity Of The Vacnt Arraysmentioning
confidence: 83%
“…The growth conditions (gas flow, heating and cooling rate, water flow, etc.) are described in [31][32][33]. TEM did not show deposition of amorphous carbon on the walls of the as-grown CNTs (Fig.…”
Section: Synthesis and Purity Of The Vacnt Arraysmentioning
confidence: 83%
“…The numbers of walls gradually decreased with increasing hydrogen concentration in the reaction atmosphere. It is widely accepted that catalyst particle size has a direct templating effect on the morphology and distribution of prepared CNTs [43,[47][48][49][50][51]. We speculate that the change of hydrogen concentration in the gas deposition process (by influencing the catalyst particle size) leads to changes in the diameter and number of walls in the prepared VACNTs.…”
Section: Morphological Analysis Of Vacntsmentioning
confidence: 84%
“…Insufficient hydrogen causes the oxidized catalyst Fe to be reduced incompletely, while excessive hydrogen converted the carbon production in the gas phase into the reagents, thus decreasing the overall driving force of the process [41]. Joshi et al [37,42,43] experimentally observed the role of water and hydrogen in terms of their influence on CNT growth, and point out that hydrogen controls the cracking of the carbon precursor ethylene, thereby controlling the purity as well as the number of walls of the CNTs grown. Schaber et al [44,45] investigated the tribological properties of densely-packed VACNTs and the morphology effect on the frictional coefficients.…”
Section: Introductionmentioning
confidence: 99%